Checklist and distribution of Nepomorpha (Hemiptera: Heteroptera) from China - Xie, Tong-Yin; He, Fu-Xia; Liu, Guo-Qing (Zootaxa, 2024)
An updated catalog of the infraorder Nepomorpha from China is provided based on literature reports, museum specimens, and field collections. In total, 214 species of Nepomorpha are listed in 6 superfamilies, 11 families, and 37 genera, including: Aphelocheiridae (1 genus, 27 species), Belostomatidae (3 genera, 7 species), Corixidae (9 genera, 52 species), Gelastocoridae (1 genus, 3 species), Helotrephidae (5 genera, 25 species), Micronectidae (1 genus, 28 species), Naucoridae (7 genera, 12 species), Nepidae (5 genera, 21 species), Notonectidae (4 genera, 32 species), Ochteridae (1 genus, 2 species) and Pleidae (1 genus, 5 species). Paraplea liturata (Fieber, 1844) is reported from mainland China for the first time. Distribution maps are provided for most species and are based on museum specimens and our field collections.